2018
DOI: 10.21767/2573-4466.100003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Active Aggregates of an Organic Solvent Tolerant Lipase from Marinobacter sp. EMB5

Abstract: Background: Marinobacter is a halophilic bacterial genus and a bio-geochemically important group in sea water, is generally associated with the bioremediation of hydrocarbon-rich effluents released into the salt-rich environment by various anthropogenic activities. It is a well-known lipase producer-the NCBI Protein database shows nearly 520 Marinobacter lipases. In this context, its lipase and esterase are considered important. However, their enzymatic properties in purified form have been scantily studied. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The influence of surfactants or detergents on crude MLL activity is shown in Supporting Information was noticed, while increment in the concentration of SDS (from 0.1 to 0.5%) and CTAB (from 1 to 10 mM) inhibited the lipase activity. The result obtained in this study is consistent with the findings of Hemamalini and Khare [19] where they reported extreme stability of Marinobacter sp. EMB5 lipase in CTAB, Triton X, and Tween 80, and significant inhibition of lipase activity by SDS.…”
Section: Influence Of Surfactants/detergents On Lipase Activitysupporting
confidence: 93%
“…The influence of surfactants or detergents on crude MLL activity is shown in Supporting Information was noticed, while increment in the concentration of SDS (from 0.1 to 0.5%) and CTAB (from 1 to 10 mM) inhibited the lipase activity. The result obtained in this study is consistent with the findings of Hemamalini and Khare [19] where they reported extreme stability of Marinobacter sp. EMB5 lipase in CTAB, Triton X, and Tween 80, and significant inhibition of lipase activity by SDS.…”
Section: Influence Of Surfactants/detergents On Lipase Activitysupporting
confidence: 93%
“…The possible reason is that a free enzyme is used in this paper and the reaction medium contains 0.1 mol L −1 phosphate buffer. In such a reaction system, there is an intense tendency to aggregate for the enzyme . The decrease of E with the concentration of CRL may be the factor that causes more enzyme molecules to aggregate with each other at a higher concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In such a reaction system, there is an intense tendency to aggregate for the enzyme. [49][50][51][52][53][54] The decrease of E with the concentration of CRL may be the factor that causes more enzyme molecules to aggregate with each other at a higher concentration. It is also observed from Fig.…”
Section: Effect Of Crl Concentration and Substrate Dosagementioning
confidence: 99%
“…SYBC WU-3 (pH 9.5) (Cai et al 2009) and Marinobacter sp. EMB5 (pH 9.0) (Hemamalini and Khare 2016). The enzyme showed excellent stability over a wide pH range from acidic to alkaline (Fig.…”
Section: Biochemical Properties Of An-lipasementioning
confidence: 91%
“…SYBC WU-3 (Cai et al 2009), but lower than those from Bacillus methylotrophicus PS3 (55 °C) (Sharma et al 2017), Marinobacter sp. EMB5 (50 °C) (Hemamalini and Khare 2016) and Pichia lynferdii Y-7723 (35 °C) (Kim et al 2010). Few microbial enzymes have catalytic activity at such low temperatures (Kim et al 2010), suggesting that An-lipase might be of value in processes requiring low temperature, such as cheese ripening and alcoholic beverage production (Sumby et al 2009).…”
Section: Biochemical Properties Of An-lipasementioning
confidence: 99%